GERAKAN TOKOH PEREMPUAN DENGAN TRANSENDENSI DALAM NOVEL TANAH TABU KARYA ANINDITA S. THAYF (KAJIAN FEMINSIME) - Resdianto Permata Raharjo; Yulianah Prihatin (STKIP PGRI Jombang, 2021)
This study had purpose to describe the existence of women becoming transcendence with actions of women achieving transformation in society and women follow the dominant group in the novel Tanah Tabu by Anindita S. Thayf . This study uses qualitative research. Collection techniques used library techniques by finding references or references from journals as a source of research data. Analysis techniques used qualitative research with hermeutic techniques namely reading, marking, coding and analyzing. Tanah Tabu novel is a novel that contains the values of social life set in Papua. Its society embraced a culture of patriarchy that made women under male rule. Women seem to be weak living beings, easily oppressed, unable to live independently and only obliged as housewives who serve their husbands and take care of pigs in their cages. The transcendence in the novel is demonstrated by mabel's character by being a woman achieving transformation in society and following the dominant group. Mabel's character in the novel boldly demonstrates her existence and refuses to be made an object by men. She fought for and sought to reclaim what should have been hers as a woman and a creature of God.